2021
DOI: 10.2147/cmar.s318975
|View full text |Cite
|
Sign up to set email alerts
|

lncRNA AC007207.2 Promotes Malignant Properties of Osteosarcoma via the miR-1306-5p/SIRT7 Axis

Abstract: Background Long non-coding RNAs (lncRNAs) have been implicated in initiation and development of numerous cancers. In the present study, we explored the role of lncRNAs AC007207.2 in osteosarcoma (OS). Methods Gene expression data of OS tissues was downloaded from the TARGET database. All the experiments were repeated at least three times. Data were analyzed using Perl, R, SPSS v12.0 and GraphPad Prism 8 software. Results We found lncRNA AC007… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…miR-1306-5p was found to decrease cerebral ischemia/reperfusion injury in vitro by targeting BIK [ 16 ]. It was also confirmed to regulate ameloblast differentiation by regulating genes related to amelogenesis imperfecta [ 15 ] and inhibit the malignant behavior of osteosarcoma cells [ 32 ]. However, the specific biological roles of miR-1306-5p and its indirect interactions and regulation of m6A in AML remain poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…miR-1306-5p was found to decrease cerebral ischemia/reperfusion injury in vitro by targeting BIK [ 16 ]. It was also confirmed to regulate ameloblast differentiation by regulating genes related to amelogenesis imperfecta [ 15 ] and inhibit the malignant behavior of osteosarcoma cells [ 32 ]. However, the specific biological roles of miR-1306-5p and its indirect interactions and regulation of m6A in AML remain poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al uncovered that sponging miR-1306-5p could stimulate the malignant behaviors of melanoma cells . MiR-1306-5p has also been reported to remarkably inhibits the malignant behavior of osteosarcoma cells . Thus, miR-1306-5p may play multiple roles and even contradictory roles in regulating malignant behaviors via different mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“… 52 MiR-1306-5p has also been reported to remarkably inhibits the malignant behavior of osteosarcoma cells. 53 Thus, miR-1306-5p may play multiple roles and even contradictory roles in regulating malignant behaviors via different mechanisms. However, there was no previous literature elucidating the role of miR-1306-5p in HCC progression.…”
Section: Discussionmentioning
confidence: 99%
“…Massive studies have identified that miRNAs such as miRNA-125a-5p, miRNA-125b, miRNA-152-3p, and miRNA-770 serve as upstream regulators of SIRT7 by targeting its 3′ UTR [135][136][137]. Besides, lncRNA AC007207.2 drove the upregulation of SIRT7 by sponging miRNA-1306-5p in osteosarcoma cells [138], while lincRNA p21 elevated SIRT7 levels by sponging miRNA-17-5p in vascular smooth muscle cells. SIRT7 expression was regulated by circRNA ZNF609 and circRNA PVT1 via miRNA-138-5p [139] and miRNA-125b/miRNA-200a sponging [140], respectively.…”
Section: Sirt7mentioning
confidence: 99%